Local partnerships in the social security system of the region = Partnerstwo lokalne w systemie bezpieczeństwa społecznego regionu - Łoś-Tomiak, Anna (Zielona Góra: Faculty of Economics and Management Press)
This paper looks at the state of social security through the lens of the local cross-sector partnerships. The foundations of cooperation undertaken by NGOs and the local government have been determined. The analysis was made on the example of the cooperation between the city of Zielona Góra and the NGO sector in the years 2009-2013.
Keywords: partnerstwo lokalne; organizacje pozarządowe; samorząd terytorialny; local partnerships; NGOs; local government